Blend of cassava starch and high-density polyethylene with green tea for food packaging. Issue 1 (February 2020) - Romagnolli, Cassiano MN; Leite, Gabriela P; Rodrigues, Tiago AR; Morelli, Carolina L
Plastic packagings are widely used for several food products. Considering the relatively short service lifetime of this application, it is important to perceive in the search of eco-friendly alternatives to this market, such as polymers from renewable sources, as thermoplastic starch and "green" polyethylene. The incorporation of an antibacterial agent to the packaging can extend food shelf life. Camellia sinensis is a plant with known antibacterial properties used in the preparation of "green tea." In the present work, green tea was incorporated to a blend of cassava thermoplastic starch and high-density polyethylene (HDPE) by melt extrusion, aiming application as active packaging. Films were obtained by thermopressing and characterized through infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy and tensile tests. Their antibacterial properties were evaluated against Staphylococcus aureus and Escherichia coli . The results indicated that the material developed has potential for food packaging applications. Moreover, the methodology applied for green tea incorporation in the Starch/HDPE films can be extended for many extracts from natural components, contributing to the advancement of research in the development of active packaging for food products. To the best of our knowledge, no previous work studied the properties of starch/HDPE blend with green tea.